Framing Prior Consultation in Brazil : Ethnographic Perspectives on Limits of Participation and Multicultural Politics. - Schumann, Charlotte (Kultur und soziale Praxis., 2018)
This book is a rich ethnographic and historic account of the juridification of prior consultation in Brazil. In her case study on the national regulation of ILO Convention 169, Charlotte Schumann critically examines the dynamic conflicts over competence and interpretation of this paramount safeguard mechanism for indigenous self-determination. The administrative center Brasília becomes the stage for a fierce struggle between state actors, social movements and experts over the limits of participation, the reification of cultural difference, and ways to vernacularize international human rights - leading to an intriguing discussion that interweaves law, anthropology and multiculturalist politics.